2001
DOI: 10.1093/hmg/10.18.1925
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of cardiotrophin-1 adenoviral gene transfer on neuromuscular degeneration in transgenic ALS mice

Abstract: Amyotrophic lateral sclerosis (ALS) is mainly a sporadic neurodegenerative disorder characterized by loss of cortical and spinal motoneurons. Some familial ALS cases (FALS) have been linked to dominant mutations in the gene encoding Cu/Zn superoxide dismutase (SOD1). Transgenic mice overexpressing a mutated form of human SOD1 with a Gly93Ala substitution develop progressive muscle wasting and paralysis as a result of spinal motoneuron loss and die at 5 to 6 months. We investigated the effects of neurotrophic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(35 citation statements)
references
References 43 publications
1
30
0
4
Order By: Relevance
“…Axonal degeneration was slowed and skeletal muscle atrophy was largely reduced by CT-1 treatment. Thus, adenovirus-mediated gene transfer of neurotrophic factors might delay neurogenic muscular atrophy and progressive neuromuscular defi ciency in ALS patients 56,70 . Administration of an adenoviral CT-1 vector to newborn progressive motor neuropathy mice leads to sustained CT-1 expression in the injected muscles and bloodstream, prolonged survival of animals, and improved motor functions.…”
Section: Cancermentioning
confidence: 99%
“…Axonal degeneration was slowed and skeletal muscle atrophy was largely reduced by CT-1 treatment. Thus, adenovirus-mediated gene transfer of neurotrophic factors might delay neurogenic muscular atrophy and progressive neuromuscular defi ciency in ALS patients 56,70 . Administration of an adenoviral CT-1 vector to newborn progressive motor neuropathy mice leads to sustained CT-1 expression in the injected muscles and bloodstream, prolonged survival of animals, and improved motor functions.…”
Section: Cancermentioning
confidence: 99%
“…Previous studies in animal models of motor neuron disease (SOD1, wobbler, progressive motor neuronopathy, spinal muscle atrophy) have shown that therapeutic benefits can be achieved via adenovirus-, lentivirus-, herpes simplex virus-and adeno-associated virus (AAV)-based delivery of genes such as mutant SOD1-targeted RNAi [48,49], VEGF [6], NT-3 [28], CNTF [2], GDNF [1,58], IGF-1 [34], Bcl-2 [5] and cardiotrophin-1 [13]. Clinical translation with some of these proteins has not yielded similar efficacy in human ALS patients [12,25,26,36]; however, trials have mostly involved systemic injection of protein, not viral vector-based gene delivery.…”
Section: Viral Vector Delivery As Als Therapymentioning
confidence: 99%
“…During embryonic development, approximately half of the motoneurons generated undergo programmed cell death (PCD) (Oppenheim, 1991). Motoneuron survival and differentiation depend on trophic factors secreted from target muscle fibers and Schwann cells surrounding motor axons (Bordet et al, 2001;Acsadi et al, 2002;Wang et al, 2002;Lu et al, 2003). Reductions in skeletal muscle activity improve the access of a motoneuron to target-derived trophic factors by increasing the extent to which motor axons branch and form neuromuscular synapses (Oppenheim et al, 2000b;Millecamps et al, 2001Millecamps et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%